UTILIZATION OF NATURAL MEDIA AROUND AS EFFORTS TO INCREASE ACTIVITY AND STUDENT LEARNING RESULTS IN TEXT WRITING LEARNING - Aan Nurhayati; Wikanengsih Wikanengsih (IKIP Siliwangi, 2018)
The results showed that Based on the results of process assessment and post-test results on learning Cycles I and Cycle II, it can be seen the impact of the intensity of utilization of natural media around the learning result of writing procedure text. This is evidenced by the level of student activity and mastery of the study material. In the first cycle of I meeting, the average of students activity was 47.06% and the average result was 67.65. Students who achieve mastery of 10 students with a percentage of 29.41%. In the first cycle of meeting II the average of student activity 61,76% and seen from the average of the test result of the participant is 65,20. Students who achieve the completeness of 18 students with a percentage of 52.94% in the second cycle of the meeting I the average activity of 67.65% participants and the average student test result is 73.62. learners who achieve mastery of 20 students with a percentage of 58.82%. In the second cycle of meeting II, the average of learners activity 94.12% and the average student test result is 84.25. Students who achieve mastery of 29% of learners or 85.29%, while 5 students with a percentage of 14.71% have not been completed. It can be concluded that the utilization of natural media around in learning to write text procedures can improve the activities and learning outcomes of learners.